Brecha entre cobertura poblacional y prestacional en salud: un reto para la reforma de salud en el Perú - Gutiérrez, César (2018)
Health Universal Coverage is one of the principal public policy impulsed in the last decade in our country, despite four different national administrations their importance remains in the agenda. The advances in this process are evident in the increment of the insurance coverage, that in case of Seguro Integral de Salud (SIS) was broaded from 19,4% in 2006 to 50,2% in 2015 (National Household Survey – NHS). However, it is real that while in 2006, 44,9% of affiliates to SIS sought attention for health problems in public health establishments of national, regional o local level, this proportion decrease to 31,7% in 2015. These results force us to pay attention to other factors that would be restricting the improvement in the health services access, especially in poor people protected financially. Among the challenges to increase the provisional coverage are the gap in infrastructure and health services equipment, the poor articulation of health care facilities at the primary care, the underuse of the existing public offering and poorly remunerated human resources with little or no incentives.